Optimization of Stope Structural Parameters for Steeply Dipping Thick Ore Bodies: Based on the Simulated Annealing Algorithm - Han Du; Xuefeng Li; Xuxing Huang; Yihao Yang; Shanda Duan; Tianlong Su; Xuzhao Yuan (Applied Sciences)
Stope structural parameters are of great significance for the safe production of mines. To efficiently and safely mine steeply dipping ultra-thick ore bodies, the K. Kegel strength design formula and limit analysis method were used to calculate a reasonable range of stope parameters. Considering the actual mining conditions, the mechanical responses under different structural parameters were obtained through numerical simulations based on a central composite experimental design. A regression model for maximum tensile stress, maximum compressive stress, and maximum vertical displacement was established using the second-order response surface method. The regression model was then used as the objective function, and multi-objective optimization was performed using a simulated annealing algorithm to obtain the Pareto optimal solution set. Based on practical engineering needs, a stope span of 15.0 m, a pillar width of 10.0 m, and a roof thickness of 11.9 m were determined as the optimal structural parameters, achieving a balance between safety and economic efficiency.